2022
DOI: 10.3390/healthcare10010154
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Advances in the World of Cardiovascular Imaging

Abstract: The tremendous advances in digital information and communication technology have entered everything from our daily lives to the most intricate aspects of medical and surgical care. These advances are seen in electronic and mobile health and allow many new applications to further improve and make the diagnoses of patient diseases and conditions more precise. In the area of digital radiology with respect to diagnostics, the use of advanced imaging tools and techniques is now at the center of evaluation and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Of the 21 selected review studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], a total of 14 studies specifically focused on the themes of the review [ 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 23 , 24 , 26 , 27 , 28 , 31 ], while the remaining [ 11 , 12 , 19 , 22 , 25 , 29 , 30 ] had a focus on different topics.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 selected review studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], a total of 14 studies specifically focused on the themes of the review [ 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 23 , 24 , 26 , 27 , 28 , 31 ], while the remaining [ 11 , 12 , 19 , 22 , 25 , 29 , 30 ] had a focus on different topics.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, various image-based mathematical models have been developed to assess hemodynamic significance and improve cost-effectiveness ( 27 ). In a single-center observational study, OCT-based computational analysis demonstrated a better correlation with conventional FFR than other imaging modalities, such as computational tomography or IVUS ( 6 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Technology enabled care, including digital health technology with “AI inside,” expands the reach of a limited number of clinicians to the communities where people live and, if thoughtfully deployed, improves health equity through greater access to standardized high-quality care 17 . The management of chronic disease using AI-enabled digital screening mechanisms supports earlier identification of disease progression, optimizing clinical workflows to serve patients in a timely manner with the appropriate resources 18 . Those individuals who need chronic management can be managed at home using many of the systems just discussed.…”
Section: Continuous Care and Optimized Resource Allocationmentioning
confidence: 99%